Analytical Performance of the New Siemens Affinity Chrome-Mediated Immunoassay Everolimus Assay and Its Interchangeability With the Thermo Quantitative Microsphere System for Routine Therapeutic Drug Monitoring of Patients After Solid Organ Transplantation. Issue 2 (April 2023) - Ialongo, Cristiano; Sapio, Maria; Angeloni, Antonio
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: A new homogeneous affinity chrome-mediated immunoassay (ACMIA) "EVRO" from Siemens Healthcare was evaluated for therapeutic drug monitoring of everolimus (EVL) with automated sample pretreatment and compared with quantitative microsphere system (QMS) "EVER" from Thermo Fisher Scientific. Methods: Imprecision, inaccuracy, and limit of quantitation (LoQ) of ACMIA/EVRO were verified using both hemolysate quality control (QC) samples and pooled whole blood specimens. The interchangeability of methods and the agreement of results were analyzed using 72 specimens (from 38, 30, and 4 kidney, liver, and lung transplant recipients, respectively). Results: Within-run imprecision ranged within %CV = 2.81–2.53 with pooled whole blood specimens and within %CV = 2.88–2.53 with QCs; total imprecision with QCs was within %CV = 2.14–1.51. Inaccuracy with value assigned QC was %△ = 5.36 at the 5.6 ng/mL level and %△ = 5.56 at the 11.7 ng/mL level. LoQ was 0.93 ng/mL (%CV = 10). Passing–Bablok regression showed a constant bias of 0.679 ng/mL (95% CI: 0.216–1.026) and a proportional bias of 1.326 (95% CI: 1.240–1.425). Bland–Altman analysis showed 5/72 (6.9%) paired differences exceeding the limits of agreement and 1/72 (1.4%) paired differences exceeding 1.96 SD to a combined bias of 39.9% after detrending. Conclusions: ACMIA/EVRO shows satisfactory analytical performances that comply with recommendations, but it does not fulfill requirements for interchangeability with QMS/EVER. Particularly, this new assay using sirolimus-specific antibody shows a sizable proportional bias versus the more specific comparator, which may be because of EVL metabolites. This is supported by the lack of agreement for individual differences in most samples collected at the peak concentration (C2). Therefore, further evidence is needed to support the transition of EVL level monitoring from QMS/EVER to ACMIA/EVRO without making extensive changes to both reference interval and patient's baseline.